KARAKTERISTIK DAN PENGGUNAAN LIPOPOLISAKARIDA (LPS) BRUCELLA DALAM MEDIK VETERINER - Eni Rohyati; Erda E. Rame Hau; Noviani N. Toelle; Gerson Y. I. Sakan (Partner, 2022)
Lipopolysaccharide (LPS) is a major component of cell membranes with gram negative bacteria including Brucella. The stain of B.abortus, B.melitensis, and B.suiscan be rough or smooth strains and express rough LPS (R-LPS)) or smooth LPS (S-LPS) as the main surface antigen; while, B .ovis and B.canis are two natural rough species that express R-LPS as the main antigen. R-LPS in B.abortus RB51 which is a stable R-LPS mutated from 2308 virulent S strains, while S-LPS is produced from B.abortus S1119-3 or S99 which is extracted by heating and then cooled. Both types of LPS can stimulate the humoral and innate immunity host immunity response. Those types are used as antigens in the diagnostic device and as immunogens of vaccines.  Keyword; LPS bakteri, Brucella, Medik Veteriner